A real-time KSACORS-based NRTK GNSS positioning system for Saudi coastal navigation. Issue 2 (2nd April 2020) - El-Diasty, Mohammed
ABSTRACT: Recently, the Saudi KSACORS network GNSS stations were developed by Saudi Geodetic Commission for Survey (GCS) to maintain an accurate GNSS positioning solution within Saudi Arabia coverage area. This paper evaluates the performance of real-time KSACORS-based network-RTK (NRTK) GNSS positioning solution for Saudi coastal maritime navigation and investigates whether the achieved accuracy can meet the International Maritime Organization (IMO) standards. To examine the performance of the real-time KSACORS-based NRTK GNSS positioning solution accuracy, kinematic data from a dual frequency GNSS data that collected onboard a vessel was processed with the KSACORS-based NRTK GNSS positioning techniques and compared with the post-processed PPK GNSS positioning solution. The root-mean-squares error (RMS) of the 2D horizontal position for the real-time KSACORS-based NRTK GNSS solution was estimated and was investigated whether RMS can fulfill the IMO standards for Saudi coastal maritime navigation. It is shown that the real-time KSACORS-based NRTK GNSS positioning solution fulfills IMO requirements at 95% confidence level for the three major phases identified as Ocean/Coastal/Port approach/Inland waterway, in port navigation and automatic docking with an accuracy requirement ranges from 10 to 0.1 m.